PENGARUH GAYA KEPEMIMPINAN DAN STRES KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PERBEKEL DESA SANGSIT - Adnyana, I Putu Agus; Putra, Made Yogi Ari (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2022)
The purpose of this study was to determine leadership style and work stress on employee performance in the Sangsit Village Perbekel office. As for this type of research, it is causal quantitative research. The analytical techniques used in this study are validity and reliability tests, classical assumption tests, multiple linear regression analysis and t-tests using as many as 32 samples,namely the apparatus who works in the Sangsit Village Perbekel office Office As for the results obtained, it shows that: 1. Leadership style affects the performance of employees in the Sangsit Village Perbekel Office 2. Work stress affects the performance of employees at the Sangsit Village Perbekel Office.